The Limits of Double Effect - Giebel, Heidi M. (Proceedings of the American Catholic Philosophical Association, 2015)
Ir. the decades since Anscombe re-introduced the distinction between intention and foresight into philosophical ethics, supporters and critics of the related principle of double effect (PDE) have displayed disagreement and confusion about its application and scope. The key to correct interpretation and application of PDE, I argue, is recognition of its limits: (1) the principle does not include an account of the goodness or badness of effects; (2) it does not include an account of intention; (3) PDE does not specify a particular action as right or obligatory; and (4) rhe privacy of intention limits its application in interpersonal and legal contexts. While all four of these features are "limits" in the sense that they are things PDE does not do, I argue that (a) only the fourth is a real limitation or disadvantage of the principle--and (b) none of the limits implies that the principle should be rejected.